Quit Playing Games with My Heart: Understanding Online Dating Scams - Huang, JingMin; Stringhini, Gianluca; Yong, Peng (Detection of Intrusions and Malware, and Vulnerability Assessment, 2015)
Online dating sites are experiencing a rise in popularity, with one in five relationships in the United States starting on one of these sites. Online dating sites provide a valuable platform not only for single people trying to meet a life partner, but also for cybercriminals, who see in people looking for love easy victims for scams. Such scams span from schemes similar to traditional advertisement of illicit services or goods (i.e., spam) to advanced schemes, in which the victim starts a long-distance relationship with the scammer and is eventually extorted money. In this paper we perform the first large-scale study of online dating scams. We analyze the scam accounts detected on a popular online dating site over a period of eleven months, and provide a taxonomy of the different types of scammers that are active in the online dating landscape. We show that different types of scammers target a different demographics on the site, and therefore set up accounts with different characteristics. Our results shed light on the threats associated to online dating scams, and can help researchers and practitioners in developing effective countermeasures to fight them.